The Influence Of Price, Promotions, Service Quality, Brand Image, And Product Reviews On Purchase Decisions On The Shopee E-Commerce Platform - Tamriatin Hidayah; Hary Sulaksono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to identify and analyze the influence of price, promotions, service quality, brand image, and product reviews on purchasing decisions on the Shopee e-commerce platform. The research method used was a quantitative approach with a descriptive design. The sample consisted of 60 respondents. Purposive sampling was employed, and the analysis technique used was multiple linear regression. The results of this study indicate that service quality, brand image, and product reviews were found to have a significant effect on purchasing decisions on the Shopee e-commerce platform, whereas price and promotions did not have a significant effect on purchasing decisions on the Shopee e-commerce platform; however, when considered together (simultaneously), they had a significant effect on purchasing decisions on the Shopee e-commerce platform.